The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.4314/gjpas.v15i3-4.48545
|View full text |Cite
|
Sign up to set email alerts
|

Household food demand analysis: a survey of semiurban and rural households in south-west Nigeria

Abstract: A two-stage Linear Approximate-Almost Ideal Demand Systems model was used to analyze household food demand in semi-urban and rural households in southwest Nigeria based on micro-level data from a multi-stage random sampling survey of one hundred and sixty two households. Aggregate food demand indicates inelastic sensitivity to price changes with the exception of grains. Individual food commodities, in the main, exhibit both price and income elastic behaviour. Expenditure elasticities ranged between o.6670 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
3
0
0
Order By: Relevance
“…The coefficient of household size had positive relationship with demand for rice implying that as the household size increases the demand for rice increases. This is also in line with theoretical underpinnings as it conforms to Reardon & Escoba, 2001;Omonona et al, 2009;Abdullahi et al, 2011;Musa et al, 2011;Sampson, 2013;Danquah & Egyir, 2014;Danso et al, 2014 but however, contrary to the work of Almas et al (2019) with household size negatively related to demand based on the household consumption expenditure. The R 2 for the exponential form was 0.713 which means that 71.3% of the variation in the demand for rice consumption was explained by the independent variables included in the exponential regression model.…”
Section: A Priori Expectationsupporting
confidence: 81%
“…The coefficient of household size had positive relationship with demand for rice implying that as the household size increases the demand for rice increases. This is also in line with theoretical underpinnings as it conforms to Reardon & Escoba, 2001;Omonona et al, 2009;Abdullahi et al, 2011;Musa et al, 2011;Sampson, 2013;Danquah & Egyir, 2014;Danso et al, 2014 but however, contrary to the work of Almas et al (2019) with household size negatively related to demand based on the household consumption expenditure. The R 2 for the exponential form was 0.713 which means that 71.3% of the variation in the demand for rice consumption was explained by the independent variables included in the exponential regression model.…”
Section: A Priori Expectationsupporting
confidence: 81%
“…This suggests that local rice is not a luxury in the households' food basket but a necessity, and a unit increase in the households' income would be proportionately less than the increasing demand for local rice by a magnitude of 0.02. This finding agrees with Onyeneke et al ( 39 ) and Gyimah-Brempong and Kuku-Shittu ( 40 ) that local rice is a necessity and not luxury food but disagrees with Omonona et al ( 38 ) who posited that rice is an inferior good, as indicated by the negative sign of its expenditure elasticity (−5.2837), and this is an expenditure elastic food item. This could be because what was obtainable in terms of the nation's economy at the time of their research is quite different from the present economic reality.…”
Section: Resultssupporting
confidence: 89%
“…This finding lends credence to the growing trend in households' rice consumption preference over other food items and therefore, the central position of rice in households' food basket. The higher proportion of households' expenditure on rice, both local and foreign varieties, agrees with Omonona et al's study ( 38 ) and Erhabor and Ojogho ( 23 ) also established that rice had the highest proportion of households' monthly food expenditure relative to other food items in their study. The implication is that sudden changes in households' food expenditure would affect the households' rice consumption.…”
Section: Resultssupporting
confidence: 87%